The Republic of Kazakhstan in the International Trade and Investment - Lobanova, Kristina (2017)
The thesis is aimed at the analysis of the position of the Republic of Kazakhstan in the international economic relations reflected in trade and investment. It presents Kazakhstan as a truly global player which has made a substantial breakthrough within a very short period of time. The first part examines current macroeconomic situation of the Republic and describes how significant was the progress made by the country during the last two decades after gaining the independence in 1991. The second part concentrates on the involvement of Kazakhstan in the international trade through illustration of the structure of trade in both goods and services, definition of the major partners and the membership of Kazakhstan in various agreements. The third part demonstrates the overall investment climate in the Republic and the main FDI trends based on the character of inflows and outflows, as well as the sectors of the economy which are the principal recipients of the inward FDI.